Body Composition and Leptin/Ghrelin Levels during Lenvatinib for Thyroid Cancer. Issue 1 (17th January 2020) - De Leo, Simone; Colombo, Carla; Di Stefano, Marta; Dubini, Antonella; Cozzi, Silvia; Persani, Luca; Fugazzola, Laura
Abstract : Weight loss is one of the most frequent adverse events during treatment with multikinase inhibitors, but scanty data are available on its extent and characteristics. This is the first assessment of the body composition by bioelectrical impedance analysis and of circulating leptin and ghrelin levels, in patients with advanced thyroid cancer before and at regular intervals during treatment with the tyrosine kinase inhibitor lenvatinib. Body mass index (BMI) decreased in all patients, with an average ∆ reduction of –6.4, –9.8, and –15.3% at 3, 6, and 12 months of treatment, respectively. Interestingly, in most patients, after the first year of treatment, BMI remained stable. In all patients, fat mass (FM) reduced more than fat-free mass, the highest decrement being of –60 and –16%, respectively. A decrease in the body cell mass, a parameter mainly due to muscle tissue, was observed only in patients with a vast baseline muscular mass. Total body water decreased in parallel to BMI. During treatment, leptin tightly paralleled the decrease of BMI values, consistent with the decrease in FM, whereas ghrelin levels increased upon BMI decrease. The loss of the FM accounts for the largest portion of BMI reduction during lenvatinib treatment. The increase in ghrelin could account for the BMI stabilization observed after 1 year of treatment. Nevertheless, oral nutritional supplements should be given as early as possible and athletic patients should be encouraged to maintain physical activity. In some circumstances, parenteral nutrition is required for the rehabilitation of these patients.